Incidence of Anaplasmosis in Buffaloes in and Around Navsari and Efficacy of Diagnostic Tests - Patel, HK; Patel, MD; Kalyani, IH; Kumar, Niranjan; Tyagi, KK; Sorathiya, LM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Incidence of anaplasmosis in buffaloes in and around Navsari district was studied over a period of one year (2016-17). Clinical cases with history of fever, anaemia, icterus, anorexia and progressive debility presented at Teaching Veterinary Clinical Complex, Livestock Research Station and in field were suspected for presence of haemoprotozoan infections and specially examined for anaplasmosis by Giemsa stained thin blood smear (GSTBS), cELISA and PCR. The information related to epidemiological parameters was also collected for risk factor’ analysis. The overall incidence of anaplasmosis in buffaloes in and around Navsari district was 37.50%. Comparatively higher incidence was observed in field cases (63.63%) followed by cases from TVCC (60%) and LRS (25%). Seasonwise incidence was 43.75, 39.13 and 22.22% in winter, summer and monsoon, respectively. Incidence in buffaloes aged above 3 years and below 3 years was 40.47 and 16.66%, respectively. The overall effect of place, season and age on incidence of anaplasmosis in buffaloes was non-significant. Considering PCR as gold standard, the sensitivity, specificity and accuracy of GSTBS were 44.44, 100 and 79.16 %, respectively, whereas, corresponding figures for cELISA was 100 %. Results indicated fairly presence of anaplasmosis in buffaloes in and around Navsari but difficult to diagnose with routine smear examination. Therefore, use of advanced diagnostic techniques (PCR/ELISA) is advocated for confirmatory diagnosis.
Keywords: Bovine anaplasmosis; Buffaloes; Diagnostic tests; Incidence